Numerical study of fatigue behavior of the aluminum 7075-t6 cantilever beam with angular cracks in different stress ratios - Mohammadi Dehcheshmeh, E. (Growing Science, 2020)
The numerical simulation of fatigue behavior of the Aluminum 7075-T6 cantilever beam with an angular crack has been investigated. Cracks are located separately in three different positions of the investigated beam. To predict the fatigue behavior of the cantilever beam the crack propagation was manually simulated. Compression load is applied in different stress ratios between zero and one; then, the obtained numerical results of this research are compared with the experimental results. It is observed that increasing the stress ratio increases the percentage of the fatigue life of the sample significantly. Ascending growth of fatigue life is slow and more severe by increasing of the stress ratio for the first and the third position, respectively. By increasing the stress ratio, the rate of deviation of the crack decreases and it converges to 0Â° in parallel to the width of the beam. This result is also observed with an increase in the distance from the support of beam. Furthermore, it is also revealed that by the increase in the initial length of the crack, the fatigue life initially reduces with smaller ratios. However, along the larger cracks, the decreasing ratio of fatigue life increases significantly. Â© 2021 Growing Science Ltd. All rights reserved.